PERBANDINGAN HUKUM RAHASIA DAGANG INDONESIA DENGAN AMERIKA SERIKAT (STUDI KOMPARATIF PUTUSAN MAHKAMAH AGUNG NOMOR 332 K/PID.SUS/2013) - Febrina, Monica Yesica (Jurnal Hukum & Pembangunan, 2021)
Legal protection of intellectual property is an important element in supporting creativity and trade. Indonesia has ratified the Agreementand Trade Related Aspects of Intellectual Property Rights and has enacted Law number 30 of 2000 concerning Trade Secret. Legal protection of trade secrets aims to protect business actors in trade practices both regionally and internationally. In addition,protection of trade secrets can prevent unfair business competition. Thus, business people have wider opportunities to develop their creativity and business. This research method is a normative research with comparative research type. This study examinesthe comparison of intellectual property protection laws specifically regarding trade secrets with laws in United States. The purpose of this comparative normative study to examine the extent to which the Trade Secret Act can be effective in its applicationas can be applied in the Supreme Court Decision.